2007
DOI: 10.1029/2006je002846
|View full text |Cite
|
Sign up to set email alerts
|

Hydration state of the Martian surface as seen by Mars Express OMEGA: 1. Analysis of the 3 μm hydration feature

Abstract: [1] Global mapping by the visible/near-infrared OMEGA spectrometer gives the first opportunity to study in detail the characteristics of the 3 mm hydration absorption on the surface of Mars. This feature is caused by bending and stretching vibrations of adsorbed or structural H 2 O and/or OH-bound to minerals. A specific data reduction scheme has been developed to remove the contribution of thermally emitted radiance from OMEGA spectra. With the derived albedo spectra, variations in strength and shape of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 50 publications
(120 reference statements)
8
92
0
Order By: Relevance
“…These authors also demonstrated that only the 3-µm absorption band may be used for this purpose, unless it is saturated. Surface water content on Mars shows significant variations across the planet Jouglet et al, 2007;Milliken et al, 2007). Milliken et al (2007) demonstrate that equatorial regions are the driest ones with ~2-5 wt.% H 2 O, while hydration increases with latitude and may be as high as 15 wt.%.…”
Section: Reflectance Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also demonstrated that only the 3-µm absorption band may be used for this purpose, unless it is saturated. Surface water content on Mars shows significant variations across the planet Jouglet et al, 2007;Milliken et al, 2007). Milliken et al (2007) demonstrate that equatorial regions are the driest ones with ~2-5 wt.% H 2 O, while hydration increases with latitude and may be as high as 15 wt.%.…”
Section: Reflectance Spectramentioning
confidence: 99%
“…Nevertheless, some influence cannot be ruled out. For example, non-altered impact melt fragments may mask the weak metal-OH feature near 2.2 μm observed in many spectra of bright areas (e.g., Murchie et al, 1993, Beinroth andArnold, 1996) and may contribute to the decrease in depth of the bound water band at 3 μm, which also shows significant spatial variations (Bibring et al, 1989Murchie et al, 1993;Calvin, 1997;Jouglet et al, 2007;Milliken et al, 2007). Recent analysis showed that a broad weak absorption band centered near 1.8 μm is present in most OMEGA spectra of bright regions (Le Mouélic et al, 2006;Combe et al 2008).…”
Section: Implications For Mars and Conclusionmentioning
confidence: 99%
“…Thermodynamic models of ice stability [e.g., (7)] and equilibration models of various hydrous minerals [e.g., (8,9)] have ruled out some simple explanations for the origin of this water reservoir. Although hydrated sulfates and clay minerals have been detected from orbit, they cover only a small fraction of the entire surface (10)(11)(12) and, to the extent of what can be observed by remote sensing, are limited to bedrock outcrops (13,14), whereas the hydration of the topmost microns of the regolith probed by the Visible and Infrared Mineralogical Mapping Spectrometer (OMEGA) aboard the European Space Agency's Mars Express orbiter is global and usually unrelated to bedrock exposures (6,15). Therefore, the nature and origin of this global hydration remain largely unknown.…”
Section: Soil Diversity and Hydration As Observed By Chemcam At Gale mentioning
confidence: 99%
“…Hematite-bearing plains (Ph unit) are at the top of a section of layered material (referred as etched terrains E unit) that is hundreds of meters thick and extends beneath the Opportunity landing site; these etched terrain materials sit unconformably on the late Noachian dissected cratered terrain materials (Hynek et al, 2002;Arvidson et al, 2003;Edgett, 2005). OMEGA data covering the etched terrains show enhanced water bands at 1.9 and 3.0 µm (Jouglet et al, 2007;Poulet et al, 2008) and, in some where discrete stratigraphic horizons are exposed Griffes et al, 2007).…”
Section: Derived Mineralogymentioning
confidence: 99%